Early Development of ADHD and ODD Symptoms from the Toddler to Preschool Years. Issue 10 (August 2022) - Brown, Hallie R.; Laws, Holly B.; Harvey, Elizabeth A.
Objective: ADHD and ODD are commonly co-occurring, but often studied individually. This study evaluated common trajectories of these disorders and explored how they co-develop in early childhood. Method: Community parents ( N  = 273) completed online surveys about their 2-year-old. Children's inattention, hyperactivity/impulsivity, and oppositional defiant disorder symptoms over 2 years were examined using latent class, dual trajectory, and cross-lagged analyses. Results: Most children followed low symptom trajectories. A small portion showed high, moderate, or increasing trajectories. The hyperactive/impulsive domain of ADHD showed a declining symptoms group. Children in high ODD groups were likely to be in high ADHD symptom groups; the converse was true but probabilities were lower. Hyperactive/impulsive symptoms predicted ODD symptoms across time, more than vice versa. Conclusion: The study extends the small body of literature assessing early development of ADHD and ODD. Findings suggest that earlier intervention for symptoms of ADHD may mitigate risk of developing ODD.